Uncovering the Ethical Dilemma of Creative Accounting Practices in Micro Enterprises from the Perspective of Internal Stakeholders - Putri Mutira; Iqbal Palestin; Sri Purwanto (Dinasti Publisher, 2025)
The practice of creative accounting in micro enterprises is often an adaptive strategy to maintain business continuity in the midst of economic pressures and limited resources, but this practice also raises significant ethical dilemmas from the perspective of governance and financial statement integrity. This research aims to uncover the ethical dilemmas faced by internal stakeholders including business owners, financial staff, and operational managers in understanding and responding to creative accounting practices in the micro business environment. Using a qualitative approach with exploratory case studies, data was collected through in-depth interviews with six informants from three micro-enterprises in the West Java region who were selected purposively. Data analysis was carried out with thematic methods to identify thought patterns, ethical justifications, and internal decision-making dynamics. The results show that creative accounting practices are often seen as pragmatic solutions to access funding, meet fiscal targets, or maintain a business's reputation, even though it is realized that it has the potential to violate the principles of honesty and accountability. Internal stakeholders face tensions between business interests and professional ethical values, which are influenced by financial literacy levels, external pressures, and organizational culture. The conclusion of this study emphasizes the importance of strengthening ethical awareness and internal governance in micro enterprises as a contribution to the development of more responsible accounting practices, as well as as the basis for the formulation of assistance and education policies for micro business actors.